Analisis Prioritas Menggunakan Metode SWOT Dalam Rencana Induk Pembangunan Kepariwisataan Kabupaten Bangli - Putra, I Gusti Ngurah Bagus Ananda Maha; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p15, 2024)
Bangli Regency has a significant potential in the tourism sector. This potential can be seen from its geographical conditions and the state of the region occupied by the surrounding community. Generally, the potential of Bangli Regency mainly comes from the tourism and agricultural sectors which must be paid attention to by the community, stakeholders and government. The government needs to engage stakeholders and tourism actors in planning tourism development and formulating strategies that align with the local conditions and potentials such as natural tourism, cultural tourism, historical tourism and religious tourism, also the government providing training and skills development for tourism actors, such as tour guides , hotel managers, culinary entrepreneurs, and other related workers, as well as promoting tourism activities, which is an opportunity because it can attract tourists to come to visit Bangli Regency. Additionally, active participation of the community as tourism actors is also crucial in developing tourist attractions by involving them in decision making, training and education regarding the tourism industry which will help increase the economic benefits obtained by the community. The objective of this research is to analyze the priorities in the master plan for the tourism development of Bangli Regency. The strategic analysis utilizes John M. Bryson's strategic planning and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. This research is a descriptive-qualitative study. The information determination technique is purposive sampling. The research results in the WO (Weaknesses, Opportunity) alternative strategy. The improvement alternative strategy involves strengthening internal weaknesses and maximizing opportunities with the hope of prioritizing tourism development areas in Bangli Regency. Keywords: Tourist Attractions, SWOT Analysis, Bangli Regency